Analysis of the Capability of Pile Assembly Foundations in Soft Soil in Physical Modeling of Variationsiin Laboratory Scale Distances - Rahman, Arief; Fatnanta, Ferry; Satibi, Syawal (ASTONJADRO, 2023)
The capacity of raft foundations, pile foundations and pile rafts on soft soil with variations in the distance between the piles. Perform analysis of the carrying capacity and settlement of each foundation test and then compare the results of the theoretical carrying capacity research with the analysis of carrying capacity calculations. The implementation of the test prepares the test along with samples of the raft foundation, pile foundation and pile raft foundation. The test were carried out using a gradual load then a dial gauge is placed at both ends of the sample raft and the load reading is taken. The pile foundation was tested with a decrease of 10 cm while the settlement on the raft foundation and the pile raft foundation was 3 cm, the carrying capacity of the raft foundation was 24 kg, the pile foundation varied 4D distances; 6D and 8D, namely 7.5 kg and the foundation of the pile raft with variations in 4D distance; 6D and 8D are 26 ; 32 and 32 kg. In the interpretation method, the pile raft foundation with various distances increased from 4D to 6D but decreased in 8D. Pile raft foundations with various distances between pile have not a significant effect where raft foundations are more dominant in supporting resistance than pile foundations.